Analisis Pemaparan Radiasi Terhadap Profil Hematologi Pekerja Radiasi Divisi Radiologi Rumah Sakit Dr. Kariadi Semarang. - Suhaedi, Eddi; Sulistiyani, Sulistiyani; Setiani, Onny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACT Background : In responding to the increasing community demand for radiological service, Dr. Kariadi Hospital has increased its modern radiological equipment, both for diagnostic and terapeutic services. To ensure quality radiation services, special knowledge and skills are required to protect the safety of both the radiation workers and the patients from hazardous radiation exposure for routine blood circulation or haematology, especially white blood cell ( leucocyte ) which are very sensitive towards biological effect of ionic radiation. Radiation impact my cause biological change in the muscles, in the form of direct action which may destroy macro biological molecule and inderect action through DNA wich impact the descendants of the radiation workers. This research also to know about the different count of leucosyt while of the radiation exposure of operation of x-ray mechine at Dr. Kariadi Hospital semarang. Therefore it is neccessary to conduct research is exfected to be used as an initial reference of the routin check â€“ up each radiation worker. Methods : The method used is explanatory reserach with cross-sectinal approach, and written questionnaires as well as interviews of the respondents to attest differences t-tes is used whle for analysis of lenght of contact with radiation source, correlation test of rank Sperman. The amount of samples is 62 person from radilogical division, 31 person of radiation workers as with radiation source as : radiologist, radiograher, engineer, and physicist other is nnot direct contact whit source of radiation as : nurse, servant. Use of free random wityhreal catagories of samples, the differences pf haematology profile were analysed by t test and the corelation Test of Rank Spearman. Results : There was significant correlation between lenght of radiation and different count of total leucosyte, eosinophyl, segment, monocyte,and lympocyte. Observation during the research periodeÂ June 2002 until Nopember 2003 ), reveals that on 90 % occation, the approns were not used by radiation workers eventhough approns were available in each radiation treatment rooms. Conclusions : based on the result of this research it can be concluded that it seem there is a significant differences of haematological profile between direct contact radiation workers and not direct contact radiation workers. Recomendation annual check-up of radiation workers ( in accordance with Goverment Regulation No. 63 of the year 2000 ), must ecarried out with more consistency and comprehensive haematological profile. Â Key words :Profile of haematology, radiation exposure, radiation worker